Islamic Law and Its Implications for Modern World - Mahsun Mahsun (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2011)
Judul Buku                  :           Islamic Law and Its Implications for Modern WorldKarangan                     :           Sayed Hassan AminPenerbit                       :           Scotland U.K., Royston Ltd, 10 Crown Road North,                                                GlasgowTahun Penerbitan        :           1989 M.Tebal                           :           399 halaman, termasuk indeks